Analysis of Defect and Quality Improvement for O Ring Product Through Applying DMAIC Methodology - Uly Amrina; Helmy Firmansyah (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2019)
To control the quality of a product to meet standards, a reliable measurable technique is needed with the company's business strategy. This research raises case studies identifying quality problems and effective ways of improvement of O Ring products using DMAIC (Define-Measures-Analyse-Improve-Control) quality control methods. Company X found the problem in the form of an average O Ring product defect ratio reaching 1.50% (the company's target is 1.30%). DMAIC is a systematic methodology that focuses on the key factors that control the performance of a process, set it at the best level and keep it at that level. Statistical tools combined with quality principles are applied to each of the DMAIC phases. In the define phase, flowcharts, critical to quality trees, and voice of customer lists are used which produce five types of defects in curing process. In the measure phase, the sigma value combined with pareto diagram are used and shows that the current sigma value is 4,178 with the biggest defect is flow-mark for the O Ring type ZZ00000123. In phase analysis, the root causes of the problem are searched using the why-why analysis and cause-effect diagrams and finds out that the causes are un-sticky rubber tip and unstandardized rubber cutting length. In the improve phase, DOE-based experiments are conducted to get the ideal rubber tip and cutting length conditions. Finally, the work standard is revised in the control phase and monitored by check sheets and control charts. The result of this DMAIC implementation was the O Ring products defect dropped to 0.83% and the sigma value rose to 4,363.Keywords: quality, DMAIC, O Ring, defect, sigma, standard